PROFIL TOKOH IBU DALAM NOVEL IBUK KARYA IWAN SETYAWAN - Purwanasari, Intan; Hayati, Yenni; Nst., Muhammad Ismail (Jurnal Bahasa dan Sastra, 2017)
The purpose of this study to describe the profile of mother figures in Ibuk's novel by Iwan Setyawan. The type of this research is qualitative research by using descriptive method based on content analysis. The object of this research is the text of Ibuk novel by Iwan Setyawan. The data collection technique is done by reading and understanding the novel of Ibuk by Iwan Setyawan, marking the special sections on the profile of the characters, and inventorying data about the mother character profile in Ibuk novel by Iwan Setyawan using format. The data analysis is done by (1) identifying the data already collected, whether it describes the aspects studied or not, (2) classifying or analyzing the data that can be abstracted as the profile data of figures using the format, (3) interpreting the data, that is interpreting the data already Collected, (4) draw conclusions and (5) write reports. The results of this study indicate that the profile of mother figures in Iwan Setyawan's Ibuk novel, namely: (a) women who have a passionate spirit, hardworking women, gentle and humble women, loving women, (b) the profile of family figures that is, women as faithful wives, women as struggling mothers, women as loving grandmothers and profiles of figures in society as simple women and in religion as women who always remember Allah.Â Keywords: novel, women, profile figure